Influence of pectin hydration on internal friction and viscosity of their aqueous solutions - Z. N. Khatko; S. A. Titov; I. A. Saranov; N. N. Korysheva; A. A. Ashinova; E. M. Kolodina (Новые технологии)
In the work the effect of hydration on the viscosity and internal friction of pectin solutions has been studied. The dynamic viscosity has been measured on a rotational viscometer, and internal friction on a torsion pendulum with a small vibration amplitude. Hydration has been studied using thermogravimetric method and differential scanning calorimetry. It has been revealed that internal friction in pectin solutions and their dynamic viscosity depend on the type of pectin substances and their combinations. The data obtained are explained on the basis of ideas about the movement of the pectin molecule, which is carried out in the form of sequential movement along the totality of potential wells formed by neighboring hydrated molecules. In addition, it has been shown that internal friction in suspensions of citrus dietary fiber in the concentration range of 1.2-2 % is determined mainly by dissipative processes in a dispersion medium, which is a solution of pectin. The presented data on the viscosity and internal friction of solutions of various types and combinations of pectins and their relationship with hydration make it possible to control rheological properties of food systems with the addition of pectin substances.